Per Jacobsson Lecture : Society, Economic Policies, and the Financial Sector. (per Jacobson lecture, 2013)
The future of finance, and in particular saving it from a popular backlash against the global financial crisis and related crisis management policies, has become a matter of great concern. In this brochure, which presents in written form a lecture from the Per Jacobsson Foundation's lecture series, former Reserve Bank of India Governor Y. V. Reddy explores three interrelated issues of particular concern to central bankers in the search for good finance for the future: how to ensure that the financial sector serves the society better, how to integrate financial sector policies better with national economic policies, and how to ensure that the financial industry functions as a means and not as an end in itself. The question-and-answer session following the lecture is also included in the brochure.